Dans un système fédéral le gouvernement central doit-il essayer d’imposer l’harmonisation fiscale? - Bélanger, Gérard (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractAfter an examination of the various forms of income tax sharing in federal countries, the paper summarizes the arguments in favour of fiscal harmonization and the means of achieving it. Finally it raises objections to both the objective of fiscal harmonization and the need to impose it.Imposed harmonization appears to be a source of monopolization that increases the discretionary power of the public sector over the citizen by facilitating tax collection. It works against economic efficiency which requires preserving the onerous character of taxation. However, harmonization may simply be the spontaneous result of the desire of government to minimize the inefficiency costs of their taxes. For example, regional governments avoid excessive differentiations in corporate taxes to avoid scaring off business.